ANALYSIS OF THE INFLUENCE OF FUNDAMENTAL FINANCIAL FACTORS OF MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY ON SHARE PRICES IN ISSI - Wulandari Wulandari; Romi Iskandar; Faznil Husna S. Rasyad (Jurnal Scientia, 2023)
Analysis of financial fundamentals is one of the methods commonly used by investors in assessing a company, in which this analysis is more based on financial ratios. This research was conducted to determine the effect of financial fundamental analysis on stock prices. The Financial Fundamental Analysis used in this study are Current Ratio (CR), Return On Assets (ROA), Debt To Equity Ratio and Price Earning Ratio (PER). This research is a quantitative study in which the population of this study is a manufacturing company in the consumer goods industry sector registered at ISSI. The sampling technique in this study used a purposive sampling technique with a total sample of 20 companies and the 2017-2021 research period. The results of this study indicate that the CR variable does not affect stock prices,while the ROA, DER and PER variables affect stock prices.